Peran Karya Cipta Indonesia Dalam Perlindungan Hak Cipta Lagu Yang Digunakan Secara Komersial(Studi Perlindungan Hukum Terhadap Lagu) - Herlambang, Dhiko; , Inayah, S.H., M.H (2016)
This research aims to know the role of Karya Cipta Indonesia (KCI) in performing the song's copyright protection as set forth in Act No. 28 by 2014 about copyright. KCI is the collective management institutions in the form of a non-profit legal entity the task and authority which are giving a license, royalty collection, as well as conducting surveillance against the user of the copyrighted songs from the works of the creator or copyright holder who has been a member of the KCI. The methods used in this research is the empirical juridical method, with this type of research is descriptive research. The data source is composed of primary data and secondary data. Method of data collection through the study of the literature and interviews, then analyzed with a qualitative method of analysis. Based on the results of the study can be obtained from the conclusion that the moment KCI has been in accordance with as regulated in Act No. 24 by 2014 about copyright and authority from KCI to appear because of a power of Attorney between copyright holders or creators with KCI.